Implementasi Model Problem Based Lerarning Dalam Mata Pelajaran Bahasa Indonesia - Ilyas, Haryadi; Simega, Berthin; Tanduk, Rita (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The aim of this research is to describe the planning, implementation and assessment of learning outcomes of the problem based learning model in Indonesian language subjects for class V SDN 011 Tatoa. The research was conducted as a qualitative type of research and used a case study approach. Data collection procedures were carried out using observation, interviews and documentation methods. Data analysis techniques using data collection, data reduction, data presentation, and drawing data conclusions. The research results found in this study are that educators need to understand CP in learning planning, formulate TP, and compile ATP and then design teaching modules. Creating teaching modules containing learning models according to learning materials. Educators have applied a problem-based learning model in one of the materials "Becoming a World Citizen". The learning implementation consists of initial activities, core activities based on PBL syntax, and closing activities. Evaluation of learning by educators every three months, and students at the end of learning, middle or end of level and semester.